Understanding Consumer Loyalty in the Digital Era: The Role of Experience, Brand Image, and Price Perception in Grab's Online Transportation Services - Diana Rosalinda Kusuma Dewi; Hesti Respatiningsih; Anes Arini (Digital Innovation : International Journal of Management, 2026)
This research aims to analyse the influence of consumer experience, brand image, and price perception on consumer loyalty in Grab's online transportation service using a quantitative approach. The study involved 103 respondents and employed various analyses, including instrument quality tests, classical assumption tests, multiple linear regression, t-tests, f-tests, and the coefficient of determination. The results indicate that consumer experience does not affect loyalty, whereas brand image and price perception positively impact consumer loyalty. These findings highlight that loyalty towards Grab's online transportation service is more strongly influenced by brand image and price perception than consumer experience alone. The study offers insights for Grab to optimise its brand image, maintain competitive pricing, and deliver excellent service to enhance consumer loyalty